2010
DOI: 10.1021/ja102043e
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Deprotonation of N-Boc Piperidine: React IR Monitoring and Mechanistic Aspects

Abstract: The high yielding asymmetric deprotonation trapping of N-Boc piperidine is successfully realized using s-BuLi and a (+)-sparteine surrogate. Monitoring of the lithiation by in situ React IR allowed the direct observation of a prelithiation complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
86
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(93 citation statements)
references
References 18 publications
5
86
0
2
Order By: Relevance
“…approximately at 1605 cm -1 , which we consider arises from the initial lithiated species 5aLi and 5cLi, or 12aLi and 12cLi. Recently reported in situ IR studies of the lithiation of a carbamate directly observed the "pre-lithiation complex" between the substrate and lithiating agent, [29] the existence of which had previously been deduced by kinetic studies on a related compound. [30] However, with ureas 5a and 5c we were unable to detect any transient intermediates between 5 and 5Li.…”
Section: In-situ Ir Spectroscopymentioning
confidence: 95%
“…approximately at 1605 cm -1 , which we consider arises from the initial lithiated species 5aLi and 5cLi, or 12aLi and 12cLi. Recently reported in situ IR studies of the lithiation of a carbamate directly observed the "pre-lithiation complex" between the substrate and lithiating agent, [29] the existence of which had previously been deduced by kinetic studies on a related compound. [30] However, with ureas 5a and 5c we were unable to detect any transient intermediates between 5 and 5Li.…”
Section: In-situ Ir Spectroscopymentioning
confidence: 95%
“…25 In situ IR spectroscopy was particularly useful here because it allowed the real-time monitoring of the reactions, providing instant feedback with regards to reaction progression, and was especially useful when reactions were conducted under air-and moisture-sensitive conditions. 26 It was, therefore, ideal for the investigation of the formal [4+2]-cycloaddition reaction as outlined in Eqn. 9, in order to gain mechanistic insight into this reaction.…”
Section: Proposed Mechanism For the Formal [4+2]-cycloadditionmentioning
confidence: 99%
“…Enantioselective synthesis of N-Boc piperidines can also be realized by using two complementary approaches developed by O'Brien, Coldham, and Gawley. The first approach is by asymmetric deprotonation in the presence of (+)-sparteine surrogate that provides a more reactive complex with s-BuLi, as demonstrated by in situ IR monitoring, with respect to other chiral ligands (i.e., (−) sparteine) [41]. Alternatively, a protocol based on a dynamic thermodynamic resolution has been developed.…”
Section: Six-membered Rings: Lithiated Piperidinesmentioning
confidence: 99%